EXPERIENCES IN SOLVING URBANIZATION PROBLEMS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article discusses the processes of urbanization, the problems they cause, and the experience of Latin America, Japan, South Korea, China, and India.